Job Demands and Job Resources in Human Service Managerial Work An External Assessment ThroughWork Content Analysis - Corin, Linda; Björk, Lisa (Nordic Journal of Working Life Studies, 2016)
Managers’ psychosocial working conditions are important for managerial sustainability in the public sector. The job demands-resources (JD-R) model is a widely applied and well-recognized framework for measuring psychosocial working conditions. However, there is still a need for methodological contributions including more objective as well as qualitative ways to assess these conditions. In this study, job demands and job resources as well as the balance between them was qualitatively and externally assessed for first-line human service managers using a work content analysis method. Conditions and actions were focused upon with an external perspective. Special attention was paid to concrete examples and consequences of work characteristics with predefined criteria and cut-off points to guide the assessments. The results reveal an imbalance for human service managers between high levels of job demands and the lack of job resources available to meet these demands. Work overload, conflicting and unclear goals and tasks, emotional demands, restricted control, and lack of supervisory and organizational support generally characterized the managerial assignment. The analysis provided concrete explanations of the current work strain in this group of employees, thereby giving both short-term and long-term possibilities for improvement of managerial work and sustainability.